2023
DOI: 10.3390/jfb14060324
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Based Temporary Implants: Potential, Current Status, Applications, and Challenges

Abstract: Biomedical implants are important devices used for the repair or replacement of damaged or diseased tissues or organs. The success of implantation depends on various factors, such as mechanical properties, biocompatibility, and biodegradability of the materials used. Recently, magnesium (Mg)-based materials have emerged as a promising class of temporary implants due to their remarkable properties, such as strength, biocompatibility, biodegradability, and bioactivity. This review article aims to provide a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 160 publications
0
11
0
Order By: Relevance
“…[45,55,56] The investigations demonstrated that MAO-produced and Sr-P coatings have high degradation resistance, while CaP coatings can improve wear resistance. [57] Microstructural evolutions can also lead to significant changes in Mg-based biomaterials, for or hydroxyapatite (HA) [163,168] Tissue engineering scaffolds Mg-based coatings with controlled degradation rate and osteogenic ability Fluorohydroxyapatite (FHA) coating on magnesium alloys [163,171] Drug delivery systems Mg-based coatings with pH-responsive and sustained-release properties Degradable polymer coatings, silk fibroin coatings, and hierarchical hybrid coatings [163,167,172] www.advancedsciencenews.com www.aem-journal.com example, grain refinement by utilization of equal channel angular pressing or other variants of severe plastic deformation methods may enhance both the mechanical properties and degradation rate; this can lead to the fabrication of denser and thicker coating layers with improved corrosion resistance. [12,[58][59][60][61][62] In addition to the usual previous methods, new techniques and procedures have been proposed, invented, and studied for the better development of multifunctional coatings, such as plasma-induced thermal-field-assisted crosslinking deposition (PTCD) that is an environment-friendly method, enabling the fabrication of hierarchical textures with potential for the simultaneous growth of the inorganic layer and organic layer.…”
Section: Introductionmentioning
confidence: 99%
“…[45,55,56] The investigations demonstrated that MAO-produced and Sr-P coatings have high degradation resistance, while CaP coatings can improve wear resistance. [57] Microstructural evolutions can also lead to significant changes in Mg-based biomaterials, for or hydroxyapatite (HA) [163,168] Tissue engineering scaffolds Mg-based coatings with controlled degradation rate and osteogenic ability Fluorohydroxyapatite (FHA) coating on magnesium alloys [163,171] Drug delivery systems Mg-based coatings with pH-responsive and sustained-release properties Degradable polymer coatings, silk fibroin coatings, and hierarchical hybrid coatings [163,167,172] www.advancedsciencenews.com www.aem-journal.com example, grain refinement by utilization of equal channel angular pressing or other variants of severe plastic deformation methods may enhance both the mechanical properties and degradation rate; this can lead to the fabrication of denser and thicker coating layers with improved corrosion resistance. [12,[58][59][60][61][62] In addition to the usual previous methods, new techniques and procedures have been proposed, invented, and studied for the better development of multifunctional coatings, such as plasma-induced thermal-field-assisted crosslinking deposition (PTCD) that is an environment-friendly method, enabling the fabrication of hierarchical textures with potential for the simultaneous growth of the inorganic layer and organic layer.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of Mg can be ameliorated through various means, one of which is alloying [ 10 , 11 ]. Alloying elements should be nontoxic or have extremely low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The Mg13Sn alloy has garnered substantial attention in the biomedical field, particularly in the context of implants [ 23 ]. The alloy’s unique mechanical properties, combined with its high biocompatibility and excellent biodegradability, make it an ideal candidate for orthopedic and other types of implants [ 24 ]. A significant area of research regarding this alloy is its machining properties, including milling [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%